Recent updates on GPCR biased agonism - Pupo, Andre S. [UNESP]; Duarte, Diego A.; Lima, Vanessa [UNESP]; Teixeira, Larissa B.; Parreiras-e-Silva, Lucas T.; Costa-Neto, Claudio M. (Elsevier B.V., 2016)
G protein-coupled receptors (GPCRs) are the most important targets for drug discovery and not surprisingly similar to 40% of all drugs currently in the market act on these receptors. Currently, one of the most active areas in GPCRs signaling is biased agonism, a phenomenon that occurs when a given ligand is able to preferentially activate one (or some) of the possible signaling pathways. In this review, we highlight the most recent findings about biased agonism, including an extension of this concept to intracellular signaling, allosterism, strategies for assessment and interpretation, and perspectives of therapeutic applications for biased agonists. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: GPCR; 7TMR; Functional selectivity